Mortality from coronary heart disease-trends for the Republic of Ireland. Issue 699 (January 1984) - Hickey, N.; Mulcahy, R.; Daly, L.; Graham, I.
Abstract : A study of certified mortality between 1968 and 1981 indicates that mortality from all causes commenced to decline from the mid 1970s in the Republic of Ireland. This trend was apparent for both sexes and for all ages except for men aged 55-64 years. A similar trend of lesser magnitude is suggested for coronary heart disease mortality in males, but not in females. The decrease in the percentage of male cigarette smokers in the population which is also reflected in a marked decline of smoking among male coronary patients, may be related to the trends in mortality.